Improving healing capability of the thermoplastic composites reinforced with carbon fibres in a Single Lap Joint (SLJ) using a co-cured method - Ferhat Kadioglu (International Journal of Lightweight Materials and Manufacture)
Thermoplastic composites as emerging materials for aerospace and automotive industries are suitable for mass-production and recycling. Healing is one of their inherent features when being damaged. This study aims to focus on the fusion bonding of a thermoplastic composite reinforced with carbon fibers. The material was fabricated in the Single Lap Joints (SLJs) configuration using a co-cured manufacturing method. First, the joints were subjected to quasi-static tensile tests to failure. The pristine joints with a 20 mm overlap length gave an average maximum load of about 5.5 kN. Then, the damaged joints were healed and subjected to the same test conditions to see their performance. It was observed that the thermoplastic adherends were able to be healed almost fully, giving a joint strength of about 5.2 kN, implying about 5 % of a decrement. Numerical works were also undertaken to see stress distributions in the joint and to predict the joint failure. Further investigations have shown the lap shear performance of such joints could be improved through different designs with no additional weight in the joint, which is feasible using the co-cured manufacturing methods.